Study of infrared thermorgrapy in evaluate the characteristics of concrete grade based on thermal insulation - Nurul Lyana, Al-Zahaba (2015)
Active infrared thermography (IRT) has been knowing and been established as a reliable non destructive and faster tools to investigates structure building. Application of infrared thermography in non destructive method is well known in civil engineering to detect voids in concrete, to check the concrete strength and material composition of concrete and grade of concrete. With help of image processing using colour detector software and IRT analysis system to assess and evaluate the concrete become more accurate and easier. Infrared thermography can be use in application of concrete studies because concrete has very small thermal conductivity and mostly limited to passive investigations quality of thermal insulation in structural building. Normal concrete cube specimens size (150mm x 150mm) were prepared with varying grade which is grade 25, grade 30, grade 35, grade 40, grade 45 and grade 50. The concrete cube condition must be in clean and free from dirt and IRT camera will be place opposite the concrete cube with computer to evaluate the data analysis. Using the IRT Camera to record and scan the concrete cube and set the equipment controls so that an adequate temperature image is viewed and recorded. This procedure need to be repeated for all concrete grade 25, concrete grade 30, concrete grade 35, concrete grade 40, concrete grade 45, concrete grade 50 and every concrete grade need two sample for each concrete grade. The concrete cube need to heating up 24 hours (110°) before test begin. The tests and image captured using IRT Camera right after the concrete come out from oven and after four (4) hour later to see the if that any change of the concrete image cause by the thermal insulation. Every changes of colour due to the thermal insulation should be recorded. Once data are collected, the results should be shown as visual image and analysed using colour IRT analysis system based on colour detector software.